Optical characterisation of Southern Ocean phytoplankton - Morrison, Frieda (Department of Oceanography, 2023)
Retrieving the optical properties of Southern Ocean (SO) phytoplankton with high confidence is critical to understanding the role of the Biological Carbon Pump (BCP). Satellite-based ocean colour remote sensing radiometry is the only observational capability that can provide synoptic views of upper ocean phytoplankton characteristics, at high spatial and temporal resolution of approximately 1 km globally, and a daily temporal resolution over a period of years to decades, as is required for climate studies. In many cases, these are the primary systematic observations available for chronically undersampled marine systems such as the SO. Inversion algorithms are applied to satellite radiometry with the goal of characterising the optical properties of the in-water constituents, primarily phytoplankton. If the relationship between Inherent Optical Properties (IOPs) and biophysical phytoplankton assemblage characteristics, in terms of abundance, cell size and pigment composition, is well understood, biogeochemical information can be inferred from satellite-derived phytoplankton IOPs. This approach has greatly augmented global comprehension of climate change and the carbon cycle. The SO is typified by unique phytoplankton optical properties, distinct from those elsewhere in the world. Most notably among these is displaying characteristically “depressed” phytoplankton absorption spectra. It is understood that there are two main drivers behind this: unusually large cell sizes, and elevated pigment density resulting from physiological changes in response to the often low light environment (photoacclimation). The primary aim of this study is to investigate the observed seasonal variability in measured in situ SO IOPs, in conjunction with the UCT-CSIR1 Equivalent Algal Populations (EAP) model of phytoplankton optical properties, to better understand the causal drivers of the optical differentiation of SO phytoplankton absorption. The EAP model is used to illustrate the biophysical source of the observed unique absorption characteristics, showing that the flattening of the spectra is driven primarily by photophysiological changes occurring during photoacclimation, namely increased density of intracellular chlorophyll a. The satellite-derived OC-CCI2 phytoplankton absorption product, observed to reproduce elevated spectra more typical of other oceans, is investigated to determine this. The model is then used to simulate biophysically consistent phytoplankton backscatter, in order to investigate whether photoacclimation, resulting in the distinctive absorption properties of the SO, has any impact on phytoplankton backscatter and the magnitude of its contribution to the bulk water-leaving signal. A reduction in phytoplankton backscatter signal was demonstrated by the model. Discussion was made in the context of opportunities for the detection of constituent IOP retrievals and biogeochemical parameters from satellites in space.